Arizona Reclaimed Water Regulation: The Future is Now - Kruse, Michael J. (Arizona-Nevada Academy of Science, 1991)
From the Proceedings of the 1991 Meetings of the Arizona Section - American Water Resources Association and the Hydrology Section - Arizona-Nevada Academy of Science - April 20, 1991, Northern Arizona University, Flagstaff, Arizona === Legal, legislative, technical and conservation factors have created a significant amount of reclaimed water reuse in Arizona. Critical recent events include: * Passage of the 1980 Groundwater Management Act * Arizona Department of Water Resources Management Plans * Passage of Environmental Quality Act * Creation of Arizona Department of Environmental Quality * 1989 Arizona Supreme Court Decision of the Status of Effluent * 1991 Arizona Reuse Rule Adoption Status